Sustainable Economic and Emission Control Strategy for Deregulated Power Systems - Palanichamy, Naveen; Kiing Ing, Wong; Kobina Danquah, Michael; Abu-Siada, Ahmed; S. Sidhu, Amandeep (International Journal of Energy Economics and Policy, 2017)
The electric power system operation and control is a multifaceted problem aims at assuring an economic, reliable, and environmentally acceptable power supply to its consumers at all times. So as to be environmentally acceptable, electric utilities are required to reduce their power plant emissions. Due to significant consumers’ responsiveness on clean electrical energy, varied operational performance schemes have developed in time. The integration of renewable energy resources, implementation of advanced pollution control equipment, adoption of multi-fuel dispatching techniques, up gradation of inefficient power generating units, and emission constraint generation scheduling are a few of them. This paper proposes a non-iterative analytical algorithm for generation scheduling of deregulated energy systems with economic and emission control strategies subject to line load ability constraints. The objectives are achieved through changes in operating and control policies only without any changes in the system configuration. Application to a modified IEEE 30-bus test system validates the suitability of the proposed control schemes for real-time implementation. Keywords: Economic control, emission control, transmission line load ability, generation scheduling, non-iterative analytical method JEL Classifications: C82, L94, P18, Q42